Prognostic capabilities and agreement of three different scores in diagnosing appendicitis in children from a developing setting. Issue 1 (January 2016) - Pinzón-Redondo, Hernando; Zarate-Vergara, Andrea; Barrios-Redondo, Katherine; Muñoz, Cesar; Guzmán, Ángel; Morales-Payares, Dorys; Alvis-Guzmán, Nelson; Paternina-Caicedo, Ángel
Abstract : Objective: The aim of this study was to assess the prognostic capabilities of the Pediatric Appendicitis Score (PAS), the Alvarado score, and the modified Alvarado score in diagnosing appendicitis in children in a developing country setting (Cartagena, Colombia). Methods: A retrospective cohort study was designed and carried out in Hospital Infantil Napoleón Franco Pareja (HINFP), a reference pediatric center in Cartagena, Colombia. Children under 18 years of age, of any sex, admitted during 2013 were included in the present study. The sensitivity and specificity of each score value in diagnosing appendicitis were estimated through the area under the receiver operative characteristics curve (AUC). Results: A total 187 patients were admitted in HINFP with abdominal pain presumptive of appendicitis. The median age of the cohort sample was 11.58 years (interquartile range, 8.33–13.61); AUC was not statistically different in the three scores assessed ( P =0.549). PAS had an AUC of 0.628 [95% confidence interval (CI), 0.495–0.763]; Alvarado score had an AUC of 0.642 (95% CI, 0.514–0.770); and modified Alvarado score had an AUC of 0.611 (95% CI, 0.471–0.751). Conclusion: Our study shows a relatively poor overall performance of the scores in diagnosing appendicitis in a developing income setting. The applicability and prognostic usefulness of the PAS, the Alvarado score, and the modified Alvarado score in developing countries should be based on the stratification of appendicitis risk in the pediatric population.